2013
DOI: 10.2106/jbjs.k.00202
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Medial Comminution and Calcar Restoration in Varus Collapse of Proximal Humeral Fractures Treated with Locking Plates

Abstract: The data suggest that medial comminution is a predictor of poor stability of proximal humeral fractures and that stability may be improved through calcar restoration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
65
0
5

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(75 citation statements)
references
References 39 publications
(54 reference statements)
5
65
0
5
Order By: Relevance
“…This may, in part, be explained by the ability to insert longer calcar screws when the plate is more proximally positioned, and/or by the presumption that more of the calcar screw threads are located in the fracture fragments and/or in higher density bone, though these aspects were not investigated in the current study. The importance of calcar screws has been shown biomechanically and computationally in previous studies, and retrospectively in clinical reviews; this study's findings add to their justification by showing that these screws directly and indirectly support the function of other screws within the constructs. These findings could encourage surgeons to prioritize the placement of calcar screws over others, given their dominant role in reducing failure risk.…”
Section: Discussionsupporting
confidence: 56%
“…This may, in part, be explained by the ability to insert longer calcar screws when the plate is more proximally positioned, and/or by the presumption that more of the calcar screw threads are located in the fracture fragments and/or in higher density bone, though these aspects were not investigated in the current study. The importance of calcar screws has been shown biomechanically and computationally in previous studies, and retrospectively in clinical reviews; this study's findings add to their justification by showing that these screws directly and indirectly support the function of other screws within the constructs. These findings could encourage surgeons to prioritize the placement of calcar screws over others, given their dominant role in reducing failure risk.…”
Section: Discussionsupporting
confidence: 56%
“…The average neck-shaft angle after surgery in the presence of medial calcar injury indicates increased tendency of varus, but was still within normal range. Similarly, Ponce et al 20) used locked plates to treat proximal humerus fracture and reported tendencies of varus in the presence of medial calcar injury, but also that this tendency could be decreased by recovering the calcar with a screw. The period of bone union was different between the two groups, on average 6.79 weeks (SD 1.606) and 8.65 weeks (SD 2.167) in G1 and G2, respectively (p < 0.05).…”
Section: Discussionmentioning
confidence: 99%
“…It is stated that, the angular stable implant was responsible for screws cutting through osteoporotic humeral heads in elder patients and, was stated as 46% over 65 years old patients [5,21,24]. Anatomic reduction and restoration of the medial cortical support are crucial in order to prevent secondary varus angulation [14,26,27]. In the present study secondary varus angulation occurred in 2 without screw cut-out (Figure 1), where anatomic reduction was achieved and medial support screws were placed but tension band wiring was not performed.…”
Section: Discussionmentioning
confidence: 99%
“…There is a certain consensus on prosthetic replacement of head -split fractures, but out of these, in 3 and 4-part fractures the surgical management based on personal experience [5]. By the introduction of locking plates there used to be a substantial rise in the osteosynthesis of the 3 and 4-part proximal humeral fractures [2,7,[10][11][12][13][14]. These plates have some advantages over conventional plates such as, providing high stability allowing early rehabilitation because of angular stable construction and multidirectional locking screws anchored in humeral head, with less dissection of soft tissue and less compromising of periosteal vascularization [2,[15][16][17].…”
mentioning
confidence: 99%
See 1 more Smart Citation